IMPROVEMENT OF SOIL LIQUEFACTION BY MICRO-PILE AND SOIL GROUTING FOR LIQUEFACTION-INDUCED FLOWSLIDE: A NUMERICAL ASSESSMENT - Rinarebut Rayhansah; Muhsiung Chang; Jen Lin Hsu; Hamzah Muhammad Hamzah Fansuri; Togani Togani Cahyadi Upomo; Rini Kusumawardani (Program Studi Teknik Sipil, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2026)
Soil liquefaction is a major geotechnical hazard that can cause bearing capacity loss, lateral spreading, and flowslides, particularly in mildly sloping ground. Loose, saturated sands with shallow groundwater tables are highly vulnerable because seismic shaking induces contraction and generates excess pore water pressure (EPWP). Although several countermeasures have been proposed, systematic evaluations of micro-piles (MP) and soil grouting (GT) under mildly sloping liquefiable ground remain limited. This study addresses this gap through three-dimensional finite element simulations in OpenSeesPL using Chi-Chi earthquake loading. Design parameters considered include pile length, diameter, and spacing for MP, as well as grouting depth and improvement ratio for GT. The results show that both MP and GT effectively delay the buildup of EPWP. However, MP consistently provides better control of lateral deformation, whereas GT primarily reduces settlement but may increase inertia due to added unit weight. Sensitivity analyses highlight the critical influence of pile geometry and spacing in MP performance, and depth and improvement ratio in GT effectiveness. These findings indicate that MP is more suitable for sites prone to lateral spreading, while GT is advantageous for conditions requiring settlement control. The outcomes provide practical guidance for engineers in designing liquefaction mitigation strategies in earthquake-prone regions.